From Opposite Corners: Comparing Persuasive Message Factors and Frames in Opposing Organizations' Websites - Katie Abrams; Courtney Meyers (Journal of Applied Communications, 2012)
The U.S. animal agriculture industry has recently faced increasing pressure from organizations that seek to change or eliminate certain animal production practices. The purpose of this study was to examine and compare the persuasive messages factors present on two nonprofit organizations’ websites. The Humane Society of the United States and the Animal Agriculture Alliance have opposing missions with the former advocating for reform in animal agriculture and the latter advocating for stakeholders in animal agriculture. A content analysis of each organization’s website found that the Humane Society’s Factory Farms website had more content overall, more content regarding specific animal agriculture industries, and contained more message strategies indicative of effective persuasion than the Animal Agriculture Alliance. The data suggest that the Humane Society of the United States’ online public relations campaign appeals to both high- and low-involvement audiences on the topic of animal agriculture, while the Alliance campaign appeals primarily to high-involvement audiences.
Keywords: Website; content analysis; animal welfare; Humane Society of the United States; Animal Agriculture Alliance; persuasive communication